A 2021 Snapshot of Citizens’ Awareness and Understanding of Florida’s Irrigation Restrictions - Laura A. Warner; Michael D. Dukes; Nicholas Taylor; Deirdre Irwin; Jim Harmon (EDIS)
A new 5-page UF/IFAS numbered publication of the Department of Agricultural Education and Communication. The information presented here is intended to inform water management district personnel, utility staff, public employees, and other educators and communicators who are charged with developing policies, promoting water use efficiency, and enforcing irrigation restrictions as a water conservation tool. Written by Laura A. Warner, Michael D. Dukes, Nicholas Taylor, Deirdre Irwin, and James Harmon. https://edis.ifas.ufl.edu/wc418